Diabetes mellitus and its association with adverse in-hospital outcomes in patients with COVID-19 - Schmitt, Volker H.; Hobohm, Lukas; Sagoschen, Ingo; Sivanathan, Visvakanth; Hahad, Omar; Espinola-Klein, Christine; Münzel, Thomas; Keller, Karsten (Viruses, 2023)
Background: Diabetes mellitus (DM) represents a relevant risk factor regarding morbidity and mortality worldwide. However, only limited data exist regarding the impact of DM on the clinical outcome of patients with COVID-19 infection. Methods: All hospitalized patients with confirmed COVID-19-infection (ICD-code U07.1) during the year 2020 in Germany were included in the present study. Patients were stratified regarding the co-prevalence of DM (ICD-codes E10-E14), and the impact of DM on in-hospital case fatality and in-hospital adverse events was analyzed. Results: Overall, 176,137 hospitalizations with confirmed COVID-19 infection were documented; of these, 45,232 (25.7%) patients had an additional diagnosis of DM. Diabetic patients with COVID-19 were more often of male sex and 7 years older (median 76.0 (IQR: 66.0–83.0) vs. 69.0 (52.0–81.0) years, p < 0.001). COVID-19 patients with DM demonstrated an aggravated comorbidity profile, as reflected by a higher Charlson comorbidity index (6.0 (IQR: 4.0–8.0) vs. 3.0 (1.0–5.0), p < 0.001). Risk for pneumonia (OR 1.38 (95% CI: 1.35–1.41), p < 0.001), acute respiratory distress syndrome (OR 1.53 (95% CI: 1.47–1.60), p < 0.001), and need for intensive care (21.3% vs. 13.3%, p < 0.001) were increased in DM patients. DM was an independent risk factor for acute kidney failure (OR 1.49 (95% CI: 1.44–1.53), p < 0.001), dialysis (OR 1.56 (95% CI: 1.47–1.66), p < 0.001), mechanical ventilation (OR: 1.49 (95% CI: 1.43–1.56), p < 0.001), extracorporeal membrane oxygenation (OR 1.44 (95% CI: 1.27–1.62), p < 0.001), major adverse cardiac and cerebrovascular events (OR: 1.24 (95% CI: 1.20–1.27), p < 0.001), and in-hospital mortality (OR: 1.26 (95% CI: 1.22–1.30), p < 0.001). Conclusions: In patients with COVID-19-infection, DM is a relevant risk factor for adverse events, including mortality. The vulnerable patient group of diabetics with COVID-19 requires intense medical care and monitoring during hospitalization.